2021
DOI: 10.1021/acs.iecr.1c02799
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Niobium-Based Catalysts Supported on SBA-15 for Hydrodeoxygenation of Anisole

Abstract: The effect of adding iron, cobalt or nickel to a prepared niobium-supported catalyst using mesoporous silica SBA-15 as a support was evaluated in the hydrodeoxygenation (HDO) reaction of anisole, chosen as a model compound in lignocellulosic biomass derived bio-oil. HDO activity as well as selectivity toward O-free products were highly dependent on the catalyst formulation: Ni incorporation showed the highest anisole conversion and selectivity to deoxygenated products, followed by Co and Fe counterparts. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Solids containing Pt over SBA-15 have been studied in m-cresol HDO [22] as well. Also, the effect of rather basic dopants (niobium in this case) on properties of SBA-15 Ni catalysts carrier was also studied in anisole HDO [23]. The effect of various metals (Nb, Ru, Pd, Pt) supported on SBA-16 was tested in phenol HDO [24] as well.…”
Section: Hdo Reaction Testmentioning
confidence: 99%
“…Solids containing Pt over SBA-15 have been studied in m-cresol HDO [22] as well. Also, the effect of rather basic dopants (niobium in this case) on properties of SBA-15 Ni catalysts carrier was also studied in anisole HDO [23]. The effect of various metals (Nb, Ru, Pd, Pt) supported on SBA-16 was tested in phenol HDO [24] as well.…”
Section: Hdo Reaction Testmentioning
confidence: 99%
“…and supports stood out among many catalyst types due to their high catalytic activity. , Supports were used to disperse and stabilize active metals, which also provided deoxidation catalytic sites (e.g., Brønsted/Lewis acids and oxygen vacancies) and even interacted with active metals to generate new catalytic sites . Molecular sieves (HZSM-5, SBA-15, MCM-41, etc.) and γ-Al 2 O 3 were common acid supports, widely used in the preparation of HDO catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Finally, NiNb and Ni−ZrO 2 catalysts supported on SBA-15 silica also showed high activity in the HDO of anisole and guaiacol, respectively, with high selectivity toward CHA production. 28,29 The activity of the NiNb/SBA-15 was explained in terms of acidity, metal surface exposure, and reducibility as a function of the interaction between the phases present, 28 while the good activities and selectivities toward total deoxygenation obtained for the silica supported Ni−ZrO 2 catalysts were associated with the proximity between Ni and ZrO 2 particles when confined in the silica mesopores. 29 Summarizing the above results, it can be noted that, in general, bifunctional metal-acid catalysts show catalytic performance in HDO superior to that of their metallic counterparts supported on unmodified SBA-15 silica.…”
Section: Introductionmentioning
confidence: 99%
“…Gbadamasi et al found that Ni/Al-SBA-15 catalysts were promising for HDO of dibenzofuran (DBF) into hydrocarbons, observing a synergetic effect between Ni and the Al-SBA-15 support. Li et al tested the performance of Ni/Al-SBA-15 catalysts in eugenol HDO and observed that the activity and selectivity of the catalysts were affected by both the quantity of acid sites and the dispersion of nickel species. , Finally, NiNb and Ni–ZrO 2 catalysts supported on SBA-15 silica also showed high activity in the HDO of anisole and guaiacol, respectively, with high selectivity toward CHA production. , The activity of the NiNb/SBA-15 was explained in terms of acidity, metal surface exposure, and reducibility as a function of the interaction between the phases present, while the good activities and selectivities toward total deoxygenation obtained for the silica supported Ni–ZrO 2 catalysts were associated with the proximity between Ni and ZrO 2 particles when confined in the silica mesopores . Summarizing the above results, it can be noted that, in general, bifunctional metal-acid catalysts show catalytic performance in HDO superior to that of their metallic counterparts supported on unmodified SBA-15 silica.…”
Section: Introductionmentioning
confidence: 99%